[Laiškai] / Budzinskis (Budzyński) Vladimiras - Adomui Zavadskiui. - (:unkn) unknown (My University, 1851)
3 laiškai apie nurodytų knygų atsiuntimą.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Zawadzki, Adam, 1814-1875